Current evaluation and management of anemia in patients with inflammatory bowel disease. (2nd January 2017) - Martin, Julia; Radeke, Heinfried H.; Dignass, Axel; Stein, Jürgen
ABSTRACT: Introduction : Anemia is a common extraintestinal manifestation in IBD patients and considerably impacts disease prognosis, hospitalization rates and time lost from work. While iron deficiency anemia is predominant, combinations of hematimetric and biochemical markers enable detection and targeted therapy of other etiologies including vitamin B12/folic acid deficiencies, hemolysis, myelosuppression and pharmacotherapies. Areas covered : Current literature was searched for articles focusing on etiology, diagnostics and therapy of anemia in IBD. In the light of their own experience, the authors describe the physiology of anemia in IBD and present current evidence endorsing diagnostic and therapeutic options, focusing particularly on non-iron-related etiologies. Expert commentary : Anemia in IBD is polyetiological, reaching far beyond iron deficiency anemia. While clinicians need to be aware of the increasing pallet of diagnostic tools and therapeutic options, detailed studies are needed to develop more convenient test procedures, long-term treatment and monitoring strategies, and unified guidelines for daily practice.